ROLE OF MUSEUMS IN TOURISM DEVELOPMENT - Yuldosh Altiboyev (Web of Journals Publishing, 2024)
This article talks about the importance of museums in the development of tourism in Kashkadarya region. By analyzing the existing legal bases for the organization of museums and further development of their activities, an attempt was made to reveal the existing specific aspects of the importance of museums in the development of tourism in Kashkadarya region.
Keywords: Kashkadarya region, tourism, tourist, development, museums